Preoperative neutrophil to lymphocyte ratio and platelet to lymphocyte ratio are associated with major adverse cardiovascular and cerebrovascular events in coronary heart disease patients undergoing non-cardiac surgery - Larmann, Jan; Handke, Jessica; Scholz, Anna; Dehne, Sarah; Arens, Christoph; Uhle, Florian; Motsch, Johann; Weigand, Markus A.; Janßen, Henrike (BMC cardiovascular disorders, 2020)
Preoperative risk prediction in patients at elevated cardiovascular risk shows limited accuracy. Platelet to lymphocyte ratio (PLR) and neutrophil to lymphocyte ratio (NLR) indicate systemic inflammation. Both have been investigated for outcome prediction in the field of oncology and cardiovascular medicine, as well as risk prediction of adverse cardiovascular events in non-surgical patients at increased cardiovascular risk.